Drug induced lymphocytic colitis. Issue 3 (March 1994) - Beaugerie, L; Luboinski, J; Brousse, N; Cosnes, J; Chatelet, F P; Gendre, J P; Le Quintrec, Y
Abstract : Three cases are presented of lymphocytic colitis with chronic diarrhoea concurrent with longterm use of Cyclo 3 Fort, a phlebotonic drug used in France. The histological and immunopathological features of lymphocytic colitis are described. We show that lymphocytic colitis is drug induced, particularly in one patient where the immunopathological features of mucosal immune cell activation were induced by drug rechallenge. It is concluded that lymphocytic colitis may be drug induced, secondary to a chronic activation of the mucosal immune system by one or several components of the drug.